The Implementation of Online Learning in The New Normal Era - Rosadi, Ihwan (Jurnal Paradigma, 2022)
Indonesia is entering the era of new normal order due to the corona pandemic, and along with the rapid development of communication and information technology. The development due to the Corona Pandemic the Government of Indonesia implements the era of new normal program order has an impact on all fields, not least in the field of education. Education as the main field that prepares superior human resources so that they are able to adjust to the times, and able to compete with other countries. The corona pandemic that hit Indonesia, is not a barrier to continue the process of education that remains quality in Indonesia. The Government launched the New Normal program as a form of new life order proclaimed by the Government of Indonesia in order to continue the life of the nation and state during the transition from social restrictions or social distancing policies, due to the coronavirus pandemic that has plagued Indonesia since some time ago. In this order is intended to regulate the activities of the new Indonesian people by realizing the world of education, especially students of madrasah ibtidaiyah who live a healthy lifestyle to minimize the transmission of the corona virus during daily activities, as well as in carrying out education in Indonesia.